Toward a Democratic Conception of Human Rights - Bağatur, Sine (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2014)
It has been repeatedly stated that human rights have become the lingua franca of contemporary politics, and that thenotion of human rights is mobilized in resistance to contemporary forms of exploitation and oppression. However, at thesame time this perception of human rights as a form of politics has been accompanied by skepticism about the value andpolitical efficacy of human rights. In this essay, I investigate which philosophical conceptions of human rights areappropriate for an analysis of the justification and political efficacy of human rights within real-life rights struggles.Against the dominant conceptions of human rights, I argue for an alternative democratic conception of human rightswhich embraces the political significance of human rights within democratic politics. This conception of human rightsmoves the debate about the praxis of human rights beyond the opposition between the naturalistic and politicalconceptions of human rights that is prevalent in the mainstream philosophical literature on human rights.